Characterization of Sedimentary Anzali Sand for Static and Seismic Studies Purposes - Ahmadi, Hadi; Eslami, Abolfazl; Arabani, Mahyar (International Journal of Geography and Geology, 2015)
Anzali as one of the populated coastal cities in the Northern Iran, contains a particular type of marine sand which is worth to be investigated for many engineering practices. This particular sand is mainly composed of saturated fine grains and is highly prone to liquefaction phenomenon during seismic events. Geotechnical zonation of the subterraneous layers show that most of sandy sedimentary soils found below the surface in this area is formed by relatively clean and fine sand. In this research, the geotechnical characteristics of Anzali sand have been studied. It is done based on three sources of information, i.e. field studies, static tests and physical modeling by dynamic tests. In this regard, the overall zonation of this area has been carried out and the extent of the sandy area has been investigated. Anzali sand has been characterized by making use of a number of soil samples obtained from various parts on which, index tests have been carried out. Furthermore, based on laboratory shear tests and information gathered from in situ tests, the shear strength parameters and the critical limits for Anzali sand have been classified. Finally, large scale physical model tests were conducted to show the dynamic behavior of the sand under cyclic and dynamic loads and also the development of the excess pore water pressure during dynamic loading that could cause the liquefaction initiation.